Development and Evaluation of an Android-Based Islamic ‎Wasathiyah E-Book for Enhancing Religious Moderation and ‎Learning Outcomes Students ‎ - Suharmanto Suharmanto; Zakiyuddin Baidhawy; Supardi Supardi (Yayasan Darussalam Bengkulu, 2025)
The limited integration of digital teaching materials in Islamic Religious Education (PAI) has created a gap between students’ digital learning habits and the predominantly conventional resources used in classrooms. This study aimed to develop and evaluate an Android-based Islamic wasathiyah e-book designed to strengthen religious moderation, tolerance, and students’ learning outcomes in junior high school PAI learning. This study employed a Research and Development (R&D) design adapted from the Borg and Gall model, covering needs analysis, product development, expert validation, product revision, and implementation. Data were collected through observations, interviews, questionnaires, documentation, expert validation sheets, practicality assessments, and learning outcome tests. The feasibility and practicality of the product were analyzed descriptively, while its effectiveness was examined through a pretest–posttest design supported by statistical testing and N-Gain analysis. The findings revealed that PAI learning resources in the observed schools were still dominated by printed textbooks, while teachers strongly needed technology-integrated materials relevant to students’ characteristics. The developed e-book systematically incorporated Islamic wasathiyah values into tolerance and respect-for-differences materials through an Android-based format. Expert validation showed that the product was feasible, with content feasibility reaching 90.8% and technological feasibility reaching 81.7%. Practicality assessments also indicated highly positive responses from teachers (90.83%) and students (94.7%). The effectiveness test demonstrated improved student learning outcomes, with N-Gain results showing that most students achieved moderate improvement. These findings indicate that the Android-based Islamic wasathiyah e-book is feasible, practical, and effective for supporting PAI learning. This study contributes an empirically validated model for integrating digital learning innovation with religious moderation education in secondary schools.